Enhanced High-Performance Concrete - Hartmann, Joey (2025)
The new generation of high-performance hydraulic concrete (HPC), known as ultra-high-performance concrete (UHPC), is being evaluated at the Turner-Fairbank Highway Research Center of the Federal Highway Administration (FHWA) in McLean, Virginia, USA. The Center for Structural Laboratory is assessing two prestressed concrete slabs made with UHPC, in accordance with the tests specified by AASHTO Type II. These tests aim to evaluate the structural performance of the slabs in correlation with the performance of UHPC.